Islamic Financial Inclusion and Regional Economic Resilience : Evidence Quantile Regression FMOLS on Productivity, Poverty, Unemployment - Danial Muhammad Wirdyansyah Wirdyansyah; Aulia Fadila Nuruddin Nuruddin; Bunga Aprillia Aprillia; Neneng Hartati Hartati; Widiawati Widiawati Widiawati (Masoem University, 2026)
This study investigates the impact of Islamic Financial Inclusion Index (IFII) on regional economic resilience in Indonesia by analyzing productivity in the manufacturing sector, poverty levels, and employment rates across 33 provinces from 2014 to 2024. Using panel Quantile Regression and Fully Modified Ordinary Least Squares (FMOLS), the research examines how IFII and its interaction with education (measured by average years of schooling) influence these three development outcomes across different quantiles of financial inclusion. Provinces were grouped into five quantiles based on their IFII scores, allowing the analysis to capture heterogeneous effects across varying levels of Islamic financial access. The results reveal that IFII positively affects manufacturing output in provinces with lower financial inclusion but has a diminishing or negative effect at higher IFII quantiles. Conversely, IFII consistently reduces poverty across all financial inclusion levels, with the strongest effect in provinces with the lowest IFII. Its effect on employment appears significant only in higher inclusion quantiles, indicating that stronger financial ecosystems are more effective in supporting labor absorption. The interaction between IFII and education shows a complex pattern: it enhances industrial productivity and reduces unemployment at upper IFII quantiles but is associated with higher poverty at lower quantiles, potentially reflecting structural mismatches between education quality and financial access. FMOLS results confirm the long-run relationships between variables and reinforce the quantile-specific insights. The study emphasizes the importance of tailoring policy responses to local financial inclusion contexts to strengthen resilience, particularly by integrating financial access with education strategies in regions lagging behind.